Family Limitation - Sanger, Margaret, 1879-1966 (London : Bakunin Press, 1920)
1920 1920 1920s 16 pages : illustrations FAMILY LIMITATION 12 One can feel it is fitted by pressing the Anger around the soft part of the pessary, which should completely cover the mouth of the womb. If you do not feel the mouth of the womb through the rubber then the pessary is not on right. It should be moved backward a little or forward until the mouth can be felt covered. If you still cannot feel it then remove and use some other preventive. The uterus may be turned or tipped back so far that a pessary could not reach the cervix. [Picture] a— womb ; b— pessary covering mouth of womb ; c— vagina; d— bladder. If it is properly adjusted there will be no discomfort, the man will be unconscious that anything is used, and no germ or semen can enter the womb. It is not always necessary to take a douche until the following morning, but it is always SAFER to douche immediately after the act. Take part or about a quart of an antiseptic douche BEFORE the pessary is removed; after removing it continue the douche and cleanse thoroughly. Wash the pessary in clear cold water, dry well and place away in the box. One should last two years, if cared for. I consider the use of the pessary as one of the most convenient, as well as the cheapest and the safest method of prevention. Any nurse or doctor will teach one how to adjust it ; then women can teach each other. It is not advisable to wear the pessary all the time. Take it out after using, and wear it only when needed. A little experience will teach one that to place it is a simple matter. 15X/2/490/4